2020
DOI: 10.1039/c9gc03620b
|View full text |Cite
|
Sign up to set email alerts
|

Humin based resin for wood modification and property improvement

Abstract: This study presents a novel process of wood modification employing humins, i.e. polydisperse furanic macromolecules formed during sugar dehydration. Humin valorization is more and more in the spotlight, thanks to the increased research efforts being placed by industries on biomass valorization. Here, a water soluble liquid fraction of humins was employed to impregnate wood and was polymerized within the wood using heat. This so-called 'humination' process was compared with the more classical furfurylation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 40 publications
0
36
0
1
Order By: Relevance
“…Humins’ solution in water can be employed, for instance, to create upon thermal treatment a polyfuranic network within wood cells. This so-called ‘humination of wood’ is following the same approach as in furfurylation of wood with aqueous furfuryl alcohol (FA) solutions [ 27 ]. Pure humins foams have been prepared by applying heat under very acid conditions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Humins’ solution in water can be employed, for instance, to create upon thermal treatment a polyfuranic network within wood cells. This so-called ‘humination of wood’ is following the same approach as in furfurylation of wood with aqueous furfuryl alcohol (FA) solutions [ 27 ]. Pure humins foams have been prepared by applying heat under very acid conditions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that humins can be applied in a wide range of applications [14,15,16,17,18,19,20,21]. Lately, we demonstrated the potential of humins as thermosetting to produce all green composites [22] and for wood modification [23]. To further exploit the use of humins as thermosetting resin, the study of the curing kinetics plays a crucial role in developing and optimizing the industrial manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, furanic humins derived from the acid treatment of pure fructose have been the focus of attention for the preparation of various foams and resins [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. This interest was prompted by a Netherlands company having developed a novel process of industrialization to render commercially available this type of interesting material [ 11 ].…”
Section: Introductionmentioning
confidence: 99%